Multination states in Asia accommodation or resistance - Bertrand, Jacques 1965-.; Laliberte, Andre 1959-. (New York Cambridge University Press, 2010)
"As countries in Asia try to create unified polities, many face challenges from minority groups within their own borders seeking independence. This volume brings together international experts on countries in all regions of Asia to debate how differently they have responded to this problem. Why have some Asian countries, for example, clamped down on their national minorities in favour of homogeneity, whereas others have been willing to accommodate statehood or at least some form of political autonomy? Together they suggest broad patterns and explanatory factors that are rooted in the domestic arena, including state structure and regime type, as well as historical trajectories. In particular, they find that the paths to independence, as well as the cultural elements that have been selected to define post-colonial identities, have decisively influenced state strategies. This is a global phenomenon - and the book explains the broader theoretical and political implications - but violence and ethnic unrest have been particularly prevalent in Asia, and this is as true of China in its relationship to Tibet, as of Burma and Sri Lanka in relation to their national minorities. As the first book to analyse this phenomenon across Asia, it will attract a readership of students and scholars across a broad range of disciplines"--Provided by publisher.
Machine generated contents note: Introduction Jacques Bertrand and Andre; Laliberte;; 1. Revolutionary state formation and the Unitary Republic of Indonesia Anthony Reid; 2. The crisis of border states in India Rajeev Bhargava; 3. Pakistan: neither state nor nation Sumit Ganguly; 4. Constitutional politics and crisis in Sri Lanka Sujit Choudry; 5. The dilemmas of Burma's multinational society Ardeth Thawnghmung; 6. The double-edged sword of autonomy in Indonesia and the Philippines Jacques Bertrand; 7. China and the virtual Taiwan nation Andre; Laliberte;; 8. The failure of China's ideologies in Tibet Gary Tuttle; 9. Leninism's long shadow in central Asia Edward Schatz; Conclusion Jacques Bertrand and Andre; Laliberte;.
Keywords: Multinational states -- Asia; Asia -- Politics and government -- 1945-.